The pyrolysis behaviors of phosphorus-containing organosilicon compound modified APP with different polyether segments and their flame retardant mechanism in polyurethane foam. (15th September 2019) - Chen, Yajun; Li, Linshan; Qi, Xiaoqing; Qian, Lijun
Abstract: Two kinds of phosphorus-containing organosilicon compounds (PCOCs) with different polyether segments (polyether segment with hydroxyl, PCOC–OH; polyether segment with amino group, PCOC–NH) were synthesized. They were used to modify ammonium polyphosphate (APP), which were named as MAPP-OH and MAPP-NH. Then MAPP-OH and MAPP-NH were respectively added into the low density-rigid polyurethane foam (LD-RPUF). MAPP-NH and MAPP-OH showed better thermal stability under N2 atmosphere. The pyrolysis behavior test results showed that the PO· free radical and NH3 release temperature of MAPP-NH began earlier and the release time of NH3 lasted longer than that of MAPP-OH, which can enhance the free radical quenching effect and dilution effect in gas phase. The flame retardant LD-RPUF was characterized by the limited oxygen index (LOI) measurement, horizontal burning test and cone calorimeter test. The results showed that the LOI value of LD-RPUF/MAPP-NH was higher than that of LD-RPUF/MAPP-OH. Meanwhile, the addition of MAPP-NH also dramatically reduced the total heat release and smoke of LD-RPUF during combustion than that of MAPP-OH. Graphical abstract: Image 1